Peningkatan Kapasitas Media Konten Pemasaran Integrasi UMKM di Bandung Raya - Himawan, Abdurrahman Faris Indriya; Ratih Hendayani; Harrys Sudarmaji (JURNAL PENGABDIAN MANAJEMEN, 2025)
The concept of integrated marketing, both at the global level and at the micro, small and medium enterprise level, requires every activity to be able to adapt to customer needs and desires. Not only from what they give to their customers, but also from what they give to the people who work in that organization. The method used describes a systematic approach in the implementation of community service aimed at increasing the capacity of Micro, Small, and Medium Enterprises (MSMEs) in integrating their business marketing through the adoption of digital technology. Using a combination of qualitative and quantitative approaches, this method involves situation analysis, participant selection, implementation of digital marketing workshops, periodic implementation and mentoring, and comprehensive evaluation. The design used is quasi-experimental and will be used to measure the impact of the program on the marketing performance of MSMEs, with the aim of producing reputable scientific publications. Analysis of pre-test and post-test data from digital marketing training and assistance showed a significant increase in the capacity of MSMEs to integrate their business marketing. There was an average increase of 45% in digital knowledge, 60% in the use of digital platforms, and 30% in marketing data integration. Qualitatively, MSMEs feel a positive impact on increasing market reach and sales potential. Nonetheless, the challenges in the consistency of implementation and integrated data management still need further attention.